Astragaloside and/or Hydroxysafflor Yellow A Attenuates Oxygen-Glucose Deprivation-Induced Cultured Brain Microvessel Endothelial Cell Death through Downregulation of PHLPP-1. (15th December 2020) - Cao, Jinyi; Wang, Kai; Lei, Lu; Bai, Lu; Liang, Ruimin; Qiao, Yi; Duan, Jialin; Gao, Kai; Cao, Shanshan; Zhao, Chao; Yang, Zhifu
Abstract : The incidence of ischemic stroke, a life-threatening condition in humans, amongst Asians is high and the prognosis is poor. In the absence of effective therapeutics, traditional Chinese medicines have been used that have shown promising results. It is crucial to identify traditional Chinese medicine formulas that protect the blood-brain barrier, which is damaged by an ischemic stroke. In this study, we aimed to elucidate such formulas. Brain microvascular endothelial cells (BMECs) were used to establish an in vitro ischemia-reperfusion model for oxygen-glucose deprivation (OGD) experiments to evaluate the function of two traditional Chinese medicines, namely, astragaloside (AS-IV) and hydroxysafflor yellow A (HSYA), in protecting against BMEC. Our results revealed that AS-IV and HSYA attenuated the cell loss caused by OGD by increasing cell proliferation and inhibiting cell apoptosis. In addition, these compounds promoted the migration and invasion of BMECs in vitro . Furthermore, we found that BMECs rescued by AS-IV and HSYA could be functionally activated in vitro, with AS-IV and HSYA showing synergetic effects in rescuing BMECs survival in vitro by reducing the expression of PHLPP-1 and activating Akt signaling. Our results elucidated the potential of AS-IV and HSYA in the prevention and treatment of stroke by protecting against cerebral ischemia-reperfusion injury.